A Determination of the Risk of Ruin: Reply - Vinso, Joseph D. (Journal of Financial and Quantitative Analysis, 1981)
To sum up, Emery and Cogger [5] have raised several interesting questions concerning the derivation of the safety index (as well as the related risk of ruin) and the interpretation of that index which needed to be addressed. While the potential limitations discussed are theoretically possible, closer examination reveals that most of the concerns raised are unlikely to occur in practical applications, although certain of the procedures utilized were in need of further explanation. Several of these issues also provide extensions of the present work to make the estimation of the risk of ruin an even more robust measure of the potential for corporate failure.